Evaluasi Kapasitas Lahan Parkir pada Wilayah Kantor Besar PT Bukit Asam Tbk Tanjung Enim - Akhmad Khanif Berliana; Farlin Rosyad; Ely Mulyati (Pusat riset dan Inovasi Nasional, 2025)
The increasing number of employees and vehicles at the Head Office of PT Bukit Asam Tbk Tanjung Enim has created a growing demand for adequate parking facilities. Limited parking space tends to encourage the use of on-street parking, which may lead to traffic congestion and reduce the comfort of the office environment. This study aims to analyze parking capacity and provide optimal management recommendations. The research was conducted through a preliminary survey, literature review, collection of primary and secondary data, and descriptive analysis to determine the parking space requirements for each type of vehicle. The results show that the maximum parking duration for cars and motorcycles is 440 minutes, with peak volumes of 142 vehicles/hour for cars and 124 vehicles/hour for motorcycles at 06.00–06.59. The parking index reached 96.52% for cars and 73.33% for motorcycles. The available static capacity is 115 SRP for cars and 210 SRP for motorcycles, while the ideal parking space requirement is 122 SRP for cars and 151 SRP for motorcycles. In conclusion, the current parking capacity is sufficient for motorcycles but insufficient for cars. Therefore, optimization of parking patterns, such as adjusting the parking angle to 90°, is necessary to increase capacity and improve convenience for all employees.